The Middle-income Trap: Upaya Pembangunan Manusia dan Pentingnya Peran Pemerintah - Tasya Pramasela; Subagio Subagio (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2022)
The most important reason why the middle-income countries, including Indonesia, can't reach the level of economic growth in high-income countries is that their level of productivity is lower than high-income countries. In order to increase their productivity levels, they must primarily increase human development. The study aims to test determinants that influence human development and the importance of government intervention. The research object is middle-income countries in the period 2015–2019. Data panel is used and tested using fixed effect model approach. The results showed household consumption and government expenditure had positive effect on human development. Meanwhile, foreign direct investment and corruption have no effect on human development. The results of this study are expected to be inputs and considerations for the Indonesian government in order to create strategies and public policies that support national development that focuses on improving the capabilities and competitiveness of their people through human development.